A Morita context related to finite groups acting partially on a ring - Guzman, J.A.; Lazzarin, J. (Algebra and Discrete Mathematics, 2009)
In this paper we consider partial actions of groups on rings, partial skew group rings and partial fixed rings. We study a Morita context associated to these rings, α-partial Galois extensions and related aspects. Finally, we establish conditions to obtain a Morita equivalence between Rα and R⋆αG.